Two Highly Similar Poplar Paleo-subgenomes Suggest an Autotetraploid Ancestor of Salicaceae Plants - Liu, Yinzhe; Wang, Jinpeng; Ge, Weina; Wang, Zhenyi; Li, Yuxian; Yang, Nanshan; Sun, Sangrong; Zhang, Liwei; Wang, Xiyin (Frontiers in Plant Science, 2017)
As a model plant to study perennial trees in the Salicaceae family, the genome of poplar was sequenced, revealing recurrent paleo-polyploidizations during its evolution. A comparative and hierarchical alignment of its genome to well-selected reference genome would help understand its genome structure and gene family evolution. Here, by adopting relatively simpler grape genome as reference, and inferring intra- and inter-genomic gene colinearity, we produced a united alignment of two genomes, and hierarchically distinguished layers of paralogous and orthologous genes, related to recursive polyploidizations and speciation. We revealed homologous blocks in grape and poplar genomes and between them. Moreover, we characterized gene missing and showed that poplar had two considerably similar subgenomes (<=0.05 difference in gene deletion) produced by the Salicaceae-common tetraploidization, suggesting its autotetraploid nature. Besides, the present efforts provide a valuable data set of orthologous and paralogous genes for further study of the genome structure and functional evolution of poplar and other Salicaceae plants.